Population Contraction in Late Roman Galilee: Reconsidering the Evidence - Lapin, Hayim (Bulletin of ASOR, 2017)
Based on detailed archaeological survey, Uzi Leibner argued that there was a substantial decline in population in late antique Galilee. This article reviews the evidence from the survey, making use of standard quantitative methods, and points to non-demographic factors that have shaped the evidence on which the conclusion depends. A predominant proportion of the pottery was produced at a single site (Kefar ?ananiah), and these forms generally have a higher sherd count than non-Kefar ?ananiah forms. As sherd count is strongly correlated with the number of sites at which a form appears, assessments of the survival and population of sites based on proportions of pottery is distorted by the distribution of Kefar ?ananiah pottery, which can be shown to decline with distance. Once we control for distance, site size also appears to be an important factor in the proportions of pottery from every period. Although these factors taken together do not necessarily negate Leibner's conclusion, they do necessitate a reevaluation.